Natural Drainage Transporter System for Rainfall-Induced Residual Soil Slope Stabilisation – a review. Issue 1 (September 2020) - Baharudin, Nur Azlin; Kassim, Azman; Ahmad, Kamarudin
Abstract: The rainfall-induced residual soil slope stability issues constitute a major threat to both lives and property particularly in tropical country which characterized as intense and long duration rainfall. Capillary barrier system (CBS) is a well-known alternative in controlling the pore-water pressure built up and percolation. There were various studies has been done to improve the CBS performance but it shows that the performance of the conventional CBS under intense rainfall has not been particularly convincing. The application of transport layer with CBS as a cover to prevent percolation of rainfall infiltration into residual soil slope and landfill has been studied however the effectiveness was assured. This review article discusses the application of unsaturated drainage transport layer system as an intermediate layer at natural soil layer to divert rainfall infiltration laterally for residual soil slope stabilisation. A drainage transport system is a great alternative to increase lateral diversion capacity at the interface of Grade VI and Grade V soil slope layers and delay breakthrough occurrences.